2023
DOI: 10.21203/rs.3.rs-2588489/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of endoplasmic reticulum stress-related biomarkers of diabetes nephropathy based on bioinformatics and machine learning

Abstract: Background: Diabetes nephropathy (DN) is a growing public health concern worldwide. Renal dysfunction impairment in DN is intimately linked to ER stress and its related signaling pathways. Nonetheless, the underlying mechanism and biomarkers for this function of ER stress in the DN remain unknown. Methods: Microarray datasets were retrieved from the Gene Expression Omnibus (GEO) database, and ER stress-related genes (ERSRGs) were downloaded from the MSigDB and GeneCards database. We identified hub ERSRGs for D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Endoplasmic reticulum (ER) stress is one of the major cellular mechanisms involved in kidney injury in DN 33 . Numerous studies have demonstrated that the dysfunction of ER stress is associated with onset and progression of DN, ER stress inhibitors decreased ER stress and halted the progression of DN 34,35 . However, some studies demonstrated that activated ER stress had a protective role on DN which re ected the bidirectional control of ER stress in DN 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Endoplasmic reticulum (ER) stress is one of the major cellular mechanisms involved in kidney injury in DN 33 . Numerous studies have demonstrated that the dysfunction of ER stress is associated with onset and progression of DN, ER stress inhibitors decreased ER stress and halted the progression of DN 34,35 . However, some studies demonstrated that activated ER stress had a protective role on DN which re ected the bidirectional control of ER stress in DN 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Last several years, the global prevalence of Diabetes mellitus (DM) has been on the rise, paralleled by a gradual increase in diabetes-related diabetic kidney disease (DKD) [ 1 ]. DKD, a severe microvascular complication of DM, presents clinically with elevated blood glucose, proteinuria and diminished glomerular filtration rate [ 2 ].…”
Section: Introductionmentioning
confidence: 99%